2021
DOI: 10.3390/f12111521
|View full text |Cite
|
Sign up to set email alerts
|

Using TLS-Measured Tree Attributes to Estimate Aboveground Biomass in Small Black Spruce Trees

Abstract: Research Highlights: This study advances the effort to accurately estimate the biomass of trees in peatlands, which cover 13% of Canada’s land surface. Background and Objectives: Trees remove carbon from the atmosphere and store it as biomass. Terrestrial laser scanning (TLS) has become a useful tool for modelling forest structure and estimating the above ground biomass (AGB) of trees. Allometric equations are often used to estimate individual tree AGB as a function of height and diameter at breast height (DBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…This pattern is also observed when evaluating the correlation between the plot-level biomass and the TLS-derived metrics aggregated at the plot level. This result agrees with previous findings by [74] that compared the ability of Quantitative Structure Models (QSMs) and bounding boxing to estimate aboveground biomass in small Picea mariana (L.) trees, with a higher accuracy (R 2 adj = 0.89) for the bounding box in comparison to the QSM (R 2 adj = 0.82). In contrast, other studies such as [50,65] have demonstrated the superiority of slicing or voxelization over simpler methods in computing crown volume, crown structure, or aboveground biomass.…”
Section: Individual Correlationssupporting
confidence: 92%
“…This pattern is also observed when evaluating the correlation between the plot-level biomass and the TLS-derived metrics aggregated at the plot level. This result agrees with previous findings by [74] that compared the ability of Quantitative Structure Models (QSMs) and bounding boxing to estimate aboveground biomass in small Picea mariana (L.) trees, with a higher accuracy (R 2 adj = 0.89) for the bounding box in comparison to the QSM (R 2 adj = 0.82). In contrast, other studies such as [50,65] have demonstrated the superiority of slicing or voxelization over simpler methods in computing crown volume, crown structure, or aboveground biomass.…”
Section: Individual Correlationssupporting
confidence: 92%
“…This would be of particular value over areas where existing field data are extremely limited, and it provides opportunities to sample other vegetation types such as forested peatlands and wetlands and track recovery dynamics of burned areas. Combined with limited destructive sampling, this could enable the development of biomass models that rely on allometric predictors that can be measured from above, such as height and crown area [77]. One limitation mentioned in Section 5.4 was the estimation of AGB and age of small black spruce in peatlands.…”
Section: Future Workmentioning
confidence: 99%
“…Filter discussion; Section S5: Correlation between Topographic and Field Wetness; Figure S1: Gravimetric Soil Water Content (SWC) as a function of topography-based Saga Wetness Index (SWI) and the fitted regression lines. References [99][100][101][102][103][104][105][106][107][108][109][110][111] are cited in the Supplementary Materials. Institutional Review Board Statement: Not applicable.…”
Section: Supplementary Materialsmentioning
confidence: 99%